2022
DOI: 10.3390/v14030566
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal Shedding of Gammaherpesvirus DNA by Cats, and Natural Infection of Salivary Epithelium

Abstract: Felis catus gammaherpesvirus-1 (FcaGHV1), a novel candidate oncogenic virus, infects cats worldwide. Whether the oropharynx is a site of virus shedding and persistence, and whether oronasal carcinomas harbor FcaGHV1 nucleic acid were investigated. In a prospective molecular epidemiological study, FcaGHV1 DNA was detected by cPCR in oropharyngeal swabs from 26/155 (16.8%) of cats. Oropharyngeal shedding was less frequently detected in kittens ≤3 months of age (5/94, 5.3%) than in older animals; >3 months to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Our current study sought to build on this finding by examining, for the first time, the prevalence and quantity (viral load) of FcaGHV1 DNA in liquid saliva collected from cats. We found that 19.8% of domestic cats had detectable FcaGHV1 DNA shed in saliva, while Rose et al found a similar prevalence of 16.8% FcaGHV1 DNA-positive oropharyngeal swabs [ 22 ]. Together, these studies suggest that cats commonly shed FcaGHV1 via the oropharynx into saliva.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Our current study sought to build on this finding by examining, for the first time, the prevalence and quantity (viral load) of FcaGHV1 DNA in liquid saliva collected from cats. We found that 19.8% of domestic cats had detectable FcaGHV1 DNA shed in saliva, while Rose et al found a similar prevalence of 16.8% FcaGHV1 DNA-positive oropharyngeal swabs [ 22 ]. Together, these studies suggest that cats commonly shed FcaGHV1 via the oropharynx into saliva.…”
Section: Discussionmentioning
confidence: 81%
“…While numerous previous studies have characterized FcaGHV1 DNA prevalence in the blood (reviewed in [ 25 ]), a recent study by Rose et al [ 22 ] was the first to detect FcaGHV1 DNA shedding in the oral cavity. Our current study sought to build on this finding by examining, for the first time, the prevalence and quantity (viral load) of FcaGHV1 DNA in liquid saliva collected from cats.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations